CONCEPTUAL FOUNDATIONS AND PEDAGOGICAL CONDITIONS FOR FOSTERING TOLERANCE AMONG STUDENTS IN THE VOCATIONAL EDUCATION SYSTEM FOR TEACHING ACTIVITIES (Web of Teachers: Inderscience Research, 2025)
This article focuses on verifying the conceptual foundations of the genesis of tolerance in the context of moral and ethical training of students oriented towards professional pedagogical practice. It is argued that the professional educational process of future specialists in the field of pedagogy should be based on strategic principles for constructing positive tolerant interaction. This approach is integrated through the actualisation of professional standards, regulatory documents and ethical codes of pedagogical activity, the key element of which is a personality-oriented component. The concluding part presents an analysis of empirical data obtained in the course of an experimental study aimed at the effective formation of positive tolerant attitudes in the youth academic environment.